2012
DOI: 10.1353/hpu.2012.0088
|View full text |Cite
|
Sign up to set email alerts
|

Types of Dental Fear as Barriers to Dental Care among African American Adults with Oral Health Symptoms in Harlem

Abstract: To examine the types of dental fear experienced by African American adults and the role of these fears in the utilization of dental care, in-depth interviews were conducted with a street-intercept sample of 118 African Americans living in Harlem, New York City, who had experienced at least one oral health symptom in the past six months. Despite their oral symptoms, participants delayed or avoided dental care (often for years) due to a variety of dental fears, including fears of: 1) pain from needles; 2) the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…It has been investigated that race/ethnicity is a marker for oral health status, and underlying cultural beliefs and practices influence the condition of the teeth and mouth, through diet, careseeking behaviors, use of home remedies or attitudes towards and patterns of use of health services (Butani Y et al 2008,Siegel K et al 2012, Flores G and Vega LR 1998, so this survey-based research aims to assess the awareness, behavior and attitude of patients in a sample of Saudi population regarding endodontic treatment. This study showed (27%) of subjects know a lot about root canal treatment and(41%) of subjects have average knowledge regardless of interesting in details; this reflects increased knowledge and concern of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been investigated that race/ethnicity is a marker for oral health status, and underlying cultural beliefs and practices influence the condition of the teeth and mouth, through diet, careseeking behaviors, use of home remedies or attitudes towards and patterns of use of health services (Butani Y et al 2008,Siegel K et al 2012, Flores G and Vega LR 1998, so this survey-based research aims to assess the awareness, behavior and attitude of patients in a sample of Saudi population regarding endodontic treatment. This study showed (27%) of subjects know a lot about root canal treatment and(41%) of subjects have average knowledge regardless of interesting in details; this reflects increased knowledge and concern of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Policymakers, administrators, and insurance organizations have a major role in improving access to dental services. High cost of dental care has led to not referring patients to the clinic in many times and countries (Siegel K et al 2012) According to the World Health Organization (WHO) (21), the Saudi health care system is ranked 26th among 190 of the world's health systems. It comes before many other international health care systems in some developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanation is that other perceptions and/or barriers may have stronger influences on the behaviour that would mask the impact of the awareness on predicting dental attendance. For example, the pain perception attributed to the dental visit has hindered the care-seeking behaviors among the adults for both themselves and their [11,15]. Increased awareness about the importance of dental visits for prevention of future complicated treatments and educating parents that those visits do not necessarily cause any discomfort for their child may increase children's dental attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, lack of dental insurance reduced the odds of dental attendance significantly. Although lack of access to care including uninsured status has been the most standing barrier to dental attendance [8,11,15], the availability of care and dental insurance has not been proven to be a solo predictor of dental attendance [8]. Perceived need is another important factor that promotes care-seeking behaviour among individuals with chronic health concerns like dental problems or for prevention [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation